2017
DOI: 10.1002/1873-3468.12763
|View full text |Cite
|
Sign up to set email alerts
|

A MYB‐type transcription factor, MYB2, represses light‐harvesting protein genes in Cyanidioschyzon merolae

Abstract: While searching for transcriptional regulators that respond to changes in light regimes, we identified a MYB domain-containing protein, MYB2, that accumulates under dark and other conditions in the unicellular red alga Cyanidioschyzon merolae. The isolation and analysis of a MYB2 mutant revealed that MYB2 represses the expression of the nuclear-encoded chloroplast RNA polymerase sigma factor gene SIG2, which results in the repression of the chloroplast-encoded phycobilisome genes that are under its control. Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
(41 reference statements)
0
3
0
Order By: Relevance
“…Amongst the seven nucleus-encoded chloroplast RNA polymerase sigma factors (Gasu_29800, Gasu_17390, Gasu_43280, Gasu_54330, Gasu_44980, Gasu_28760, Gasu_35420) found in the DEGs between heterotrophy and phototrophy, two (Gasu_28760, Gasu_35420) were significantly downregulated, which would suggest that they are required for controlling expression of the chloroplast genome in heterotrophy. In Cyanidoschyzon merolae , a red microalga very close to G. sulphuraria , a MYB2 transcription factor represses the expression of the nuclear-encoded chloroplast RNA polymerase sigma factor gene SIG2, which results in the downregulation of the expression of the chloroplast-encoded phycobilisome genes ( Kawase et al, 2017 ). Only one myb-family related factor was found upregulated in heterotrophy (Gasu_46180, +1.12), which could thus be considered as a good candidate for the repression of sigma factors controlling chloroplast-encoded RNA polymerase.…”
Section: Discussionmentioning
confidence: 99%
“…Amongst the seven nucleus-encoded chloroplast RNA polymerase sigma factors (Gasu_29800, Gasu_17390, Gasu_43280, Gasu_54330, Gasu_44980, Gasu_28760, Gasu_35420) found in the DEGs between heterotrophy and phototrophy, two (Gasu_28760, Gasu_35420) were significantly downregulated, which would suggest that they are required for controlling expression of the chloroplast genome in heterotrophy. In Cyanidoschyzon merolae , a red microalga very close to G. sulphuraria , a MYB2 transcription factor represses the expression of the nuclear-encoded chloroplast RNA polymerase sigma factor gene SIG2, which results in the downregulation of the expression of the chloroplast-encoded phycobilisome genes ( Kawase et al, 2017 ). Only one myb-family related factor was found upregulated in heterotrophy (Gasu_46180, +1.12), which could thus be considered as a good candidate for the repression of sigma factors controlling chloroplast-encoded RNA polymerase.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that CPCC mRNA level in the dark was lower than that in the light under photoautotrophic condition (Kawase, Imamura, & Tanaka, 2017). Taking this result into account, we compared the HA-SPT1 protein level between Cp-SPT1 in the dark with glucose and that in the light with glucose and DCMU ( Figure 4b).…”
Section: Increased Gsspt1 Levels Accelerate C Merolae Heterotrophimentioning
confidence: 96%
“…Gene expression in higher plants is commonly regulated through the interplay of specific transcription factors and cis-acting elements. Among these, the MYB2 protein stands out, playing a crucial role in regulating processes like secondary metabolism [26,27], the meristem and pollen development [28,29], and response to abiotic stress [30]. Many experiments have been conducted to study Arabidopsis MYB2, a typical R2R3-MYB gene, and have found that it is associated with improved plant resistance to hormone and environmental stress.…”
Section: Atmyb2 Promotes Tolerance To Salt Stress By Improving Antiox...mentioning
confidence: 99%